Comparing the Blood Response to Hyperbaric Oxygen with High-Intensity Interval Training-A Crossover Study in Healthy Volunteers - Anders Kjellberg; Maléne E. Lindholm; Xiaowei Zheng; Lovisa Liwenborg; Kenny Alexandra Rodriguez-Wallberg; Sergiu-Bogdan Catrina; Peter Lindholm (MDPI AG, 2023)
High-intensity interval training (HIIT) and hyperbaric oxygen therapy (HBOT) induce reactive oxygen species (ROS) formation and have immunomodulatory effects. The lack of readily available biomarkers for assessing the dose-response relationship is a challenge in the clinical use of HBOT, motivating this feasibility study to evaluate the methods and variability. The overall hypothesis was that a short session of hyperbaric oxygen (HBO2) would have measurable effects on immune cells in the same physiological range as shown in HIIT; and that the individual response to these interventions can be monitored in venous blood and/or peripheral blood mononuclear cells (PBMCs). Ten healthy volunteers performed two interventions; a 28 min HIIT session and 28 min HBO2 in a crossover design. We evaluated bulk RNA sequencing data from PBMCs, with a separate analysis of mRNA and microRNA. Blood gases, peripheral venous oxygen saturation (SpvO2), and ROS levels were measured in peripheral venous blood. We observed an overlap in the gene expression changes in 166 genes in response to HIIT and HBO2, mostly involved in hypoxic or inflammatory pathways. Both interventions were followed by downregulation of several NF-κB signaling genes in response to both HBO2 and HIIT, while several interferon α/γ signaling genes were upregulated. Only 12 microRNA were significantly changed in HBO2 and 6 in HIIT, without overlap between interventions. ROS levels were elevated in blood at 30 min and 60 min compared to the baseline during HIIT, but not during/after HBO2. In conclusion, HBOT changed the gene expression in a number of pathways measurable in PBMC. The correlation of these changes with the dose and individual response to treatment warrants further investigation.